2016
DOI: 10.18533/jefs.v4i02.215
|View full text |Cite
|
Sign up to set email alerts
|

Still on board configuration: SEC recommendations and the efficiency of adhering firms in Nigeria

Abstract: This paper scrutinizes the effects of adherence to an encoded board configuration on firm efficiency in terms operational and financial performances using an integrated research framework that combines four distinct theories including agency, stewardship, stakeholders and resource dependency models. The research explores three main aspects of compliance outcomes; benefits accrued to conforming firms in terms of enhanced efficiency and market value, board level drivers as well as the external moderators of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 88 publications
2
15
0
Order By: Relevance
“…The paper adopted the accounting (ROA) and market value-based (Tobin's q) techniques for performance measures. Hence, ROA enables the study to draw the conclusions regarding the profitability of the firms while the Tobin's q, provides the basis for statistical inferences to investors (Lawal, 2016;Gentry & Shen, 2010). However, Firm Profitability ROA and Tobin's q were taken in line with the recommendations by prior studies (Giannarakis, 2014;Lawal, 2016;Saif-Alyousfi, Saha, & Md-Rus, 2017aBen-Amar, Chang, & McIlkenny, 2017).…”
Section: Dependent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The paper adopted the accounting (ROA) and market value-based (Tobin's q) techniques for performance measures. Hence, ROA enables the study to draw the conclusions regarding the profitability of the firms while the Tobin's q, provides the basis for statistical inferences to investors (Lawal, 2016;Gentry & Shen, 2010). However, Firm Profitability ROA and Tobin's q were taken in line with the recommendations by prior studies (Giannarakis, 2014;Lawal, 2016;Saif-Alyousfi, Saha, & Md-Rus, 2017aBen-Amar, Chang, & McIlkenny, 2017).…”
Section: Dependent Variablesmentioning
confidence: 99%
“…Importantly, most CG studies from the Arab world have largely ignored to touch the role of female directors on the board as experience has shown that a large number of these studies only concentrated on other issues while little attention was paid to this important construct. The scholars in this regard have called for further investigations on the relationship between board gender diversity and firm performance (Kakabadse et al, 2015;Kılıç & Kuzey, 2016;Lawal, 2016;Nuhu & Ahmad, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…not too large or small). There is an increased presupposition among agency theorists that moderate board size engenders effective executive monitoring and makes it difficult if not costly for the CEOs to dominate (Lawal 2016;Huang and Wang 2015). Relying on the premise of group dynamics, proponents of small board size have contended that excessive membership heightens the risk of poor communication and the emergence of splinter groups which hampers board effectiveness (Pacini et al 2008;Goodstein et al 1994).…”
Section: Board Sizementioning
confidence: 99%
“…Racial diversity is defined as the proportion of foreign directors on the board and ethnicity is defined as the ratio of three major ethnic groups in Nigeria (i.e. Hausa, Yoruba and Igbo) represented on the board (Lawal 2016;Van der Walt et al 2006). Board quality is defined as the average years of directors' professional experience including board working knowledge (Van der Walt et al 2006;Anderson et al 2010).…”
Section: Data Sources and Variablesmentioning
confidence: 99%
See 1 more Smart Citation